Comparison of effect of autologous platelet rich plasma and estrogen replacement vs estrogen replacement alone on implantation and pregnancy outcome in IUI cycles in infertility patients - Nayak, Suvendu Kumar; Pathak, Baidyanath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Successful embryo implantation requires an appropriate embryonic development coincident with a receptive endometrium. Thin endometrium, non-responsive to standard treatments is still a challenge in assisted reproductive technique, which usually results either in cycle cancellation or failed ART cycle. The minimal endometrial thickness required for implantation is now considered about 7 mm at the end of natural or medically induced follicular phase. The aim of this study is to detect any significant effect of platelet rich plasma (PRP) intrauterine infusion on endometrial proliferation, implantation and pregnancy rates. Methods: This study was carried out for a period of 12 months in a tertiary care post graduate teaching hospital. 50 patients fulfilling the inclusion criteria were divided into two groups based on randomisation. One group received PRP plus estradiol (Group P) and other group received only estradiol (Group E). All patients underwent ovulation induction with letrozole and serial monitoring of endometrial thickness was done by USG (TVS) and results were compared. Results: The mean endometrial thickness on the day of IUI in Group P was 9.1 mm+0.67 mm and in Group E was 7.56 mm+0.62 mm. The mean increase in endometrial thickness after PRP instillation was 3.4 mm+0.60 mm which is significantly higher than the Group E with mean increase of 1.5 mm+0.9 mm, which was statistically significant. However, there was no statistically significant increase in positive pregnancy rate and pregnancy outcome. Conclusions: Our study concluded that PRP instillation increased the endometrial thickness in the patients with thin endometrium. However, there was no effect on the positive pregnancy rates and outcome.